Urban rail transit coordination based on computational experiments. (1st January 2013) - Sun, Xubin; Zhang, Yue; Gao, Tongxin; Qin, Gaoyou; Dong, Hairong; Guan, Fu
This paper presents a coordination method for subway lines through passenger transfer time computational experiments with artificial transfer stations. The aim of subway lines coordination is minimising passengers' transfer time by tuning train arrival schedules of subway lines at the transfer station. Firstly, the artificial systems of two typical subway transfer stations are established, where the passengers are modelled using social force model. Secondly, computational experiments are executed with the artificial transfer stations taking train arrival time difference of subway lines as the decision variable, which is calculated to minimise passengers' average transfer time in the transfer station. Two type transfer stations are considered in this paper, the average transfer time can be reduced by 5.54% using the optimal coordination solution for subway lines.